PENGEMBANGAN MEDIA PEMBELAJARAN SERVIS BOLA VOLI KELAS IX SMPN 3 MALANG BERBASIS ANDROID MENGGUNAKAN SOFTWARE iSPRING SUITE: Volleyball, iSpring Suite, Media - Ferdiansyah, Arif; Novantua Nababan, Dandy; Wibowo Kurniawan, Ari (JURNAL ILMU KEOLAHRAGAAN, 2025)
The purpose of this research is to develop a volleyball service learning medium based on iSpring Suite for ninth-grade students at SMPN 3 Malang and to measure its validity. This is a research and development study that adopted the ADDIE model by Branch, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. Quantitative descriptive analysis was used to analyze the data collected from the research results using a questionnaire as the data collection instrument. The subjects of this study were 43 students from SMPN 3 Malang. The research product was validated by media experts, subject matter experts, and learning experts, and was also tested on both small and large groups. The results of the large group trial obtained a percentage value of 91%. Thus, this iSpring Suite-based learning media development product can be categorized as highly valid and can be utilized in the PJOK learning process at SMPN 3 Malang. It is hoped that this product can provide a tangible contribution by making it easier for ninth-grade students at SMPN 3 Malang to carry out PJOK learning, especially for volleyball service material.